Analisis Efisiensi Dan Efektivitas Sistem Kerja Enam Hari Di Unit Satuan Pengawas Internal Rumah Sakit X Semarang - Ina Qoriah; Dwi Nur Siti Marchamah; Restu Ayu Eka Pustika Dewi (Indonesian Journal of Health Community, 2025)
The six-day work system faces various challenges that need to be evaluated, particularly regarding efficiency, work-life balance, and its relevance in the modern era. While intended to enhance productivity, the additional workday often leads to fatigue, which negatively impacts work performance. An imbalance between work and personal life can affect employees' physical and mental health, ultimately reducing motivation and overall performance. The objective of this study is to analyze the efficiency and effectiveness of the six-day work system in the SPI Unit at Sultan Agung Islamic Hospital, Semarang. The study aims to understand this phenomenon within the specific context of Sultan Agung Islamic Hospital. Data collection was conducted through interviews with the Human Resources Manager, the Head of SPI, and SPI employees. The findings indicate that the six-day work system can reduce productivity, increase fatigue, and add operational costs, whereas a five-day work system is more efficient. In the digital era, a more adaptive work system is increasingly relevant to ensure regulatory compliance, improve supervision quality, and support the strategic objectives of the SPI Unit. Therefore, implementing a flexible work model that aligns with labor regulations can enhance employee well-being and improve hospital operational efficiency.